NIBR-LTSi is a selective LATS kinase inhibitor activating YAP signaling and expanding tissue stem cells in vitro and in vivo - Namoto, Kenji; Baader, Clara; Orsini, Vanessa; Landshammer, Alexandro; Breuer, Eva; Dinh, Kieu Trinh; Ungricht, Rosemarie; Pikiolek, Monika; Laurent, Stephane; Lu, Bo; Aebi, Alexandra; Schönberger, Katharina; et al. (Cell stem cell, 2024)
The YAP/Hippo pathway is an organ growth and size regulation rheostat safeguarding multiple tissue stem cell compartments. LATS kinases phosphorylate and thereby inactivate YAP, thus representing a potential direct drug target for promoting tissue regeneration. Here, we report the identification and characterization of the selective small-molecule LATS kinase inhibitor NIBR-LTSi. NIBR-LTSi activates YAP signaling, shows good oral bioavailability, and expands organoids derived from several mouse and human tissues. In tissue stem cells, NIBR-LTSi promotes proliferation, maintains stemness, and blocks differentiation in vitro and in vivo. NIBR-LTSi accelerates liver regeneration following extended hepatectomy in mice. However, increased proliferation and cell dedifferentiation in multiple organs prevent prolonged systemic LATS inhibition, thus limiting potential therapeutic benefit. Together, we report a selective LATS kinase inhibitor agonizing YAP signaling and promoting tissue regeneration in vitro and in vivo, enabling future research on the regenerative potential of the YAP/Hippo pathway.
Online verfügbar 4 April 2024, Version des Artikels 4 April 2024
Gesehen am 10.03.2025